The Penha Garcia Ichnological Park at Naturtejo UNESCO Global Geopark (Portugal): a Geotourism Destination in the Footprint of the Great Ordovician Biodiversification Event - Carlos Neto de Carvalho; Andrea Baucon; Aram Bayet-Goll; João Belo (Geoconservation Research)
Penha Garcia Ichnological Park is the most important fossil site and one of the most significant geosites of international relevance, in the territory of Naturtejo UNESCO Global Geopark. This municipal protected area is a key site for the study of trace fossil diversity at high paleolatitudes in the early stages of the Great Ordovician Biodiversification Event. Most famous among 21 ichnotaxa is Cruziana, interpreted as foraging burrows of trilobites, present in high abundance and excellent preservation. They are among the largest fossils found anywhere in the Lower Paleozoic, not uncommonly several meters long and over 20 cm wide, covering large bedding planes almost completely. The birthplace of Naturtejo Geopark is now a nature school, one of the most visited outdoor sites by schools in Portugal. It also became a reference for geotourism in this country because of the Fossil Trail that allows visitors to access a natural fossil art gallery in the Variscan-folded cliffs of the Ponsul Gorge. The Fossil Home provides the interpretation of the local geoheritage, and additional attractions are the Templar castle and church viewpoints, the climbing school, the secular watermills, the views over the lake in the heart of the syncline, and the Pego river pool. This is a major geotourism destination in the center of Portugal. The in situ conservation of fossils in this ‘outside museum’ is a challenging subject, which is being monitored using 3D high-resolution modeling of the whole gorge and the main fossil sites there to an mm-scale precision.